INTELLIGENT DECISION MAKING TOOL FOR AIDING THE SETTING OF OPTIMAL INTENSITY IN AEROBIC ENDURANCE TRAINING - Adrian PĂTRAŞCU; Monica PATRASCU; Iacob HANŢIU; Remus Cristian VĂIDĂHĂZAN (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2015)
Aerobic endurance training plays a significant part in the field of physical activity due to the fact that it has a medium intensity value and it depends primarily on aerobic energy generating processes. By engaging the cardiovascular and respiratory systems of the body this type of training is used to improve the overall endurance and fitness. The adaptation of these structures to the physical effort results in improving the performance output, by pushing the limits of cardiovascular and respiratory system’s functions. In order to obtain the desired results it is necessary to ensure the operating points that are often hard to reach by classical training methods. The human heart rate variability with respect to the velocity of walking or running presents inherent nonlinearities that are required to be taken into account when designing computer integrated training aids. This paper implements a training aiding tool for setting the optimal intensity of the training, using an intelligent decision making system for the human cardiovascular fitness. This software application was tested and validated by using pre-recorded data from various subjects and was compared to the classical way of analysing the heart rate variability of a subject. The designed intelligent decision making tool ensures the optimal desired intensity profiles, finding its usefulness in supporting the training configuration process by specialized professionals.